What Signal Paradoxes of Global Economy - T. A. Malova (Vestnik MGIMO-Universiteta)
The technological and institutional transformation of the global economy is accompanied by paradoxes that arise at its various structural levels. The global COVID-19 pandemic and its consequences have strengthened the paradoxical situations. The main paradox of globalization receives an unexpected and dramatic verification by the spread of the SARS-COV-2 virus. Disruption of international communications as the only possible way to combat the spread of infection in the short term contradicts the need to restore its interconnectedness in the long term. The institutional contradictions within global economic governance does not correspond to the digital path of the global economy development. Macroeconomic paradoxes signal the need for a transition from the dominant monetary regulation to fiscal expansion. Monetary regulation mechanisms, even in their non-traditional forms, are ineffective given the coincidence of the coronavirus pandemic with high volatility in global stock markets and oil and gas markets. Fiscal stimulation undertaken by states in the face of the spread of virus can be interpreted as a pilot project for the implementation of some of the basic ideas of the Modern Monetary Theory (MMT). The solution of the microeconomic paradox of public goods is possible on the basis of the principle of "rationality" as a priority social concept. Paradoxically, the shock of the pandemic, which “blew up” the course of things, provoked an unprecedented decline in business activity in a number of sectors of the economy, under certain conditions, can turn the vector towards economic growth and development. The paradoxes of the global economy signal that the current socio-economic model of the global economy has exhausted its endogenous development potential. Resolving paradoxical situations requires updating scientific views and patterns of their implementation. The European Commission's economic recovery plan addresses the future generation of the European Union. The shock of the coronavirus pandemic accelerates the transfer of values and technologies to the new paradigm of global world.